Effects of internal factors on surface wettability of corn stalk rind - Xun, He; Defu, Wang (International Journal of Agricultural and Biological Engineering, 2015)
Corn stalk is one of heterogeneous materials with anisotropy and variability. As the rind of corn stalk consists of rich lignin and cellulose similar to wood properties, and possessing high mechanical strength, then can be used as raw material of stalk artificial board and paper. The corn stalk rind has significant differences in fiber morphology, chemical composition and mechanical properties at different heights. Nano-SiO2 composite material contained in the epidermis of corn stalk rind is not conducive to exert adhesive into a board. To study board-making technology by intact corn stalk rind, the wettability of corn stalk rind at different sampling heights is necessary to be analyzed by keeping or removing the epidermis. To analyze the surface wettability difference, the contact angle with water, element compositions and the chemical compositions of corn stalk rind at different sampling heights were studied before and after removal of epidermis. A Fourier transform infrared (FTIR) analysis was performed. The results showed that the removal of the epidermis could significantly improve the hydrophilicity of corn stalk rind. Before removal of the epidermis, the varying contents of elements including C and Si dominate the surface wettability differences at different sampling heights of corn stalk. With an increase in the sampling height, the mass fraction of C increases while that of Si decreases, which result in increasing hydrophilicity. After removal of the epidermis, the surface wettability of corn stalk rind is mainly determined by the mass fraction of hemicellulose, and the higher the sampling height, the larger the mass fraction of hemicellulose resulting in the increase of hydrophilicity.Keywords: corn stalk rind, wettability, surface contact angle, element analysis, chemical compositions, mechanismDOI: 10.3965/j.ijabe.20150806.1996Citation: He X, Wang D F. Effects of internal factors on surface wettability of corn stalk rind. Int J Agric & Biol Eng, 2015; 8(6): 77－83.